Dynamic YAP expression in the non-parenchymal liver cell compartment controls heterologous cell communication - Liu, Kaijing; Wehling, Lilija; Wan, Shan; Weiler, Sofia Maria Elisabeth; Tóth, Marcell; Ibberson, David; Marhenke, Silke; Ali, Adnan; Lam, Macrina; Guo, Te; Pinna, Federico; Pedrini, Fabiola; et al. (Cellular and molecular life sciences, 2024)
The Hippo pathway and its transcriptional effectors yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) are targets for cancer therapy. It is important to determine if the activation of one factor compensates for the inhibition of the other. Moreover, it is unknown if YAP/TAZ-directed perturbation affects cell-cell communication of non-malignant liver cells.